Frontal cerebral atrophy associated with neurodevelopmental delay in an infant with perinatal asphyxia: a clinical case report (REVISTA CIENTÍFICA SIGNOS FÓNICOS, 2025)
Perinatal asphyxia is one of the main causes of neonatal hypoxic-ischemic encephalopathy, a condition that can lead to structural brain atrophy with significant repercussions on child neurodevelopment. We present the clinical case of a 15-month-old infant with a history of severe neonatal asphyxia, who presented with global developmental delay, microcephaly, and persistent irritability. Brain MRI showed severe bilateral frontal atrophy, ventriculomegaly, and chronic prefrontal subdural hematoma. An intensive, interdisciplinary therapeutic approach was implemented, with partial improvements in postural control and social interaction. This allowed us to illustrate the correlation between structural hypoxic damage and functional alterations, as well as the importance of early diagnosis and comprehensive intervention to improve functional prognosis.
Keywords: Perinatal asphyxia; brain atrophy; hypoxic-ischemic encephalopathy; child neurodevelopment